Need Analysis for Reconstruction of The Merdeka Belajar Kampus Merdeka Transformative Curriculum to Enhance Students’s 4C Competencies - Nasution, Aida Rahmi; Meldina, Tika; Fitriyani, Desti (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The needs analysis for reconstructing the Merdeka Belajar Kampus Merdeka-transformative curriculum of the Primary School Teacher Education program at IAIN Curup was conducted to design a transformative MBKM curriculum aimed at strengthening students’ 21st-century competencies (4C). Specifically, this study aimed to (1) explore the needs analysis for the reconstruction of the PGMI-transformative curriculum; (2) describe the stages of designing and developing the MBKM-transformative curriculum; and (3) assess the feasibility of the MBKM-transformative curriculum reconstruction based on expert validation. This study employed a Research and Development (R&D) approach following Borg and Gall’s framework with modifications from the Dick and Carey model. Data were collected through observations, interviews, and Likert scale questionnaires (1–5). The data analysis utilized both qualitative methods, including data reduction, display, verification, and conclusion drawing, and quantitative methods, employing percentage and Total Critical Response (TCR) techniques. The findings revealed: (1) The needs analysis for reconstructing the MBKM-transformative 4C curriculum, based on interviews, observations, and questionnaires, indicated that the MBKM-transformative curriculum for PGMI is “highly needed”; (2) The developed MBKM-transformative 4C curriculum design includes a conceptual draft outlining various curriculum design aspects; and (3) Expert validation of the MBKM-transformative 4C curriculum, involving experts in curriculum, language, and media, yielded a total score of 88%, indicating that the curriculum is “fit for use.”